Effects of high pressure, microwave and ultrasound processing on proteins and enzyme activity in dairy systems — A review. (October 2019) - Munir, Masooma; Nadeem, Muhammad; Qureshi, Tahir Mahmood; Leong, Thomas S.H.; Gamlath, Charitha J.; Martin, Gregory J.O.; Ashokkumar, Muthupandian
Abstract: High-pressure processing (HPP), microwaves (MW) and ultrasound (US) are used for pasteurization with minimum heat input. They also alter physico-chemical properties of milk proteins and enzymes. This article aims at identifying the important changes in milk proteins imparted by these three processing technologies. HPP dissociates casein micelles at low pH (<6.7) and concentrations (<4% w /w), while β-LG is the most pressure sensitive whey protein due to the presence of free thiol groups. Milk enzyme activity is inhibited at higher pressures (>400 MPa). MW treatment denatures whey proteins rapidly, even below their thermal denaturation temperatures. High-power MW treatment (e.g. 60 kW) deactivates enzymes by denaturing them. However, low-power controlled MW irradiation (e.g. 30 W) improves enzyme activity. Ultrasound can homogenize protein aggregates in dairy systems and cause whey protein denaturation. Sonication under applied pressure and heat (e.g. 3.5 kg/cm 2, 126.5 °C) causes enzyme inhibition while mild sonication conditions can improve enzyme activity. Industrial relevance: HPP, MW and US are gaining popularity in the dairy industry due to their ability to pasteurize and functionalize dairy streams with minimal heat input. This review offers insights into how these technologies can be used in isolation or in combination to alter milk proteins and enzyme activity for different academic and industrial applications. However, to fully understand the potential of HPP, MW and US treatment on dairy systems, further research is required in several areas including health related nutritional changes in milk and milk products caused by these technologies. Highlights: Three novel dairy processing technologies (HP, MW & US) are discussed. Impact on physical and functional properties of dairy proteins is compared. HP, MW and US can modify quality of dairy products. Comparative impact on enzyme activity is discussed.